ASPEK PSIKIATRI DALAM UPACARA KEMATIAN (MEPASAH) DI DESA TRUNYAN - Ni Nengah Tiastiningsih,; Cokorda Bagus Jaya Lesmana,; Ni Ketut Putri Ariani, (Journal of Innovation Research and Knowledge, 2025)
The Mepasah funeral ritual practiced by the Trunyan community in Bali represents a distinctive cultural tradition that differs significantly from the cremation practices commonly found in other Balinese societies. This study aims to examine the psychiatric and cultural aspects embedded in the Mepasah ritual, particularly in relation to beliefs about death, spirituality, social cohesion, and mental resilience. Using a qualitative descriptive approach based on cultural, anthropological, and psychiatric perspectives, this article explores how the Trunyan community perceives death not as an end, but as a transitional phase within the spiritual cycle of life. The ritual functions as a psychosocial mechanism that helps regulate grief, strengthen communal bonds, and maintain emotional balance among community members. The strong belief system involving ancestral spirits, sacred spaces, and ritual purity plays an essential role in shaping collective mental health and preventing prolonged psychological distress. Despite pressures from modernization and tourism, the Mepasah tradition continues to be preserved as a form of cultural identity and spiritual resilience. This study highlights the importance of integrating cultural psychiatry approaches in understanding traditional death rituals as adaptive systems that support mental well-being within indigenous communities